HUKUM BISNIS DAN PERANANNYA DALAM TRANSAKSI E-COMMERCE - Manik, Agnes Santana; Elsi Natalia Saragih; Juanda Saragih; Toman Sony Tambunan (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This research is motivated by the rapid development of e-commerce transactions in Indonesia which has given rise to various legal problems, such as unclear consumer protection, personal data security, and the validity of digital agreements. The purpose of this study is to analyze the role of business law in providing legal certainty and protection for parties involved in e-commerce transactions. This study uses a normative legal approach with a library research method, which utilizes primary and secondary legal sources. The data analysis technique used is qualitative analysis, by examining relevant laws and regulations and related court decisions. The results of the study show that business law has an important role in creating legal certainty, providing legal protection for consumers and business actors, and regulating digital dispute resolution mechanisms.